Linkages between American and European publicly traded airline companies – evidence resulting from the Diebold-Yilmaz method - Łęt, Blanka (Powiązania pomiędzy notowaniami amerykańskich i europejskich linii lotnicznych – wnioski z metody Diebolda i Yilmaza, 2020)
In this paper, the author implemented the Diebold and Yilmaz approach to analyse the connectedness between the major American and European publicly traded airline companies. The author calculated the return and volatility spillover index for the whole sample using a dynamic rolling sample analysis. The results show that all airlines are significantly linked but there is a clear division into two markets. It was found that return spillovers are more intensive than volatility spillovers. Moreover, the average connectedness level is higher in the U.S. market for returns as well as for volatility. An increase of connectedness occurred due to the certain events: issues linked with the condition of the global economy and long-term crude oil price changes
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 101-114
Keywords: airlines; connectedness; Diebold-Yilmaz approach; spillovers; linie lotnicze; powiązania; metoda Diebloda-Yilmaza; zarażanie